Transforming Value Chains for Sustainability: Closing the Loop in the Age of Electromobility - Voigt, Kai-Ingo; Czaja, Lothar; Zipse, Oliver (Springer International Publishing, 2023)
Achieving the Paris goal of limiting global warming to well below 2 °C requires radical decarbonization of our economy, including a shift to renewable energy. In the automotive sector, electromobility offers a promising option for making this transition. However, while electric vehicles (EVs) have lower emissions during their use phase, a significant part of the carbon footprint is shifted upstream in the value chain to raw material extraction and battery production. Against this background, this chapter provides an in-depth look at how the automotive industry’s transition to electromobility leads to far-reaching implications for the EV battery value chain. The chapter begins with a brief review of resource scarcity as a relevant strategic background for the circular economy. It continues with the different steps of the linear EV battery value chain. The chapter then uses a circularity perspective to discuss the technology and value chain steps for closing the loop in the EV battery life cycle. It concludes with an outlook on the challenges of circular EV battery value chains.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Battery recycling; Circular value chain; EV battery; Linear value chain; Resource scarcity; Reverse logistics